2015
DOI: 10.1186/s10194-015-0577-6
|View full text |Cite
|
Sign up to set email alerts
|

Visual evoked potentials in subgroups of migraine with aura patients

Abstract: BackgroundPatients suffering from migraine with aura can have either pure visual auras or complex auras with sensory disturbances and dysphasia, or both. Few studies have searched for possible pathophysiological differences between these two subgroups of patients.MethodsMethods - Forty-seven migraine with aura patients were subdivided in a subgroup with exclusively visual auras (MA, N = 27) and another with complex neurological auras (MA+, N = 20). We recorded pattern-reversal visual evoked potentials (VEP: 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
63
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 84 publications
6
63
0
1
Order By: Relevance
“…As a novel aspect, our study demonstrated in AwMH subjects during the interictal period a deficit of habituation of nociceptive trigeminal responses largely resembling that observed in MWoA subjects of comparable clinical severity. These data are in line with previous observations of deficit of habituation of evoked responses derived from repeated stimulation of visual cortex in subjects with migraine aura during the interictal phase . The habituation deficit of nociceptive trigeminal reflex responses in both MWoA and AwMH permits to hypothesize that these two forms of migraine share a common, probably genetically determined, pathogenic substrate.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As a novel aspect, our study demonstrated in AwMH subjects during the interictal period a deficit of habituation of nociceptive trigeminal responses largely resembling that observed in MWoA subjects of comparable clinical severity. These data are in line with previous observations of deficit of habituation of evoked responses derived from repeated stimulation of visual cortex in subjects with migraine aura during the interictal phase . The habituation deficit of nociceptive trigeminal reflex responses in both MWoA and AwMH permits to hypothesize that these two forms of migraine share a common, probably genetically determined, pathogenic substrate.…”
Section: Discussionsupporting
confidence: 91%
“…These data are in line with previous observations of deficit of habituation of evoked responses derived from repeated stimulation of visual cortex in subjects with migraine aura during the interictal phase. 21,22 The habituation deficit of nociceptive trigeminal reflex responses in both MWoA and AwMH permits to hypothesize that these two forms of migraine share a common, probably genetically determined, pathogenic substrate. However, it must be noted that in AwMH subjects, the habituation deficit of the trigeminal nociceptive reflex responses was less pronounced than that observed in subjects with MWoA, although without reaching a significant statistical level.…”
Section: Discussionmentioning
confidence: 99%
“…This findings is consistent with previous evidence obtained with psychophysiological tests [24], neuroimaging techniques [25, 26], and cortical EPs [46] showing that during the variable pain-free period between two migraine attacks, the brain of an individual with migraine is exposed to subtle cyclic functional changes. Indeed, at the cortical level, we previously observed that patients with MO and a subgroup of patients with migraine with visual aura associated with paraesthesia and/or dysphasia exhibited a strong decrease in EP amplitude habituation during the stereotyped presentation of visual stimuli with the passing of time from the last attack [4, 5]. The results of the present study revealed that the same correlation is valid for the resting excitability of the motor cortex in response to single-pulse TMS.…”
Section: Discussionmentioning
confidence: 99%
“…In a study on patients with migraine with complex aura (comprising not only visual but also sensory and language dysfunctions), a higher level of dysfunction in comparison to patients with simple aura, correlating higher interictal abnormalities with more complex aura pattern CSD, was found [57]. Also, increased VEP amplitude was correlated with a longer distance in the spreading of paroxysmal EEG responses [58].…”
Section: Aiws and Migrainementioning
confidence: 99%